The Influence Of Social Media And Brand Reputation On The Purchase Interest Of Nike Shoe Products On Generation Z Consumers In Tasikmalaya - Alfaraz, Thoriq Dzikra; Lestari, Suci Putri; Asyiah, Ai Kusmiati (Innovative Business Management Journal, 2025)
This study aims to determine the influence of social media and brand reputation simultaneously and partially on the purchase interest of Nike shoe products on Gen Z consumers in Tasikmalaya. The method used in this study is a survey method with a quantitative approach. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple linear regression analysis using SPSS software. The results of this study indicate that social media and brand reputation have a significant effect on purchase interest. Social media has a significant partial effect on purchase interest. And brand reputation has a significant partial effect on purchase interest.